Legal Policy of Disparity in Sentencing as a Ground for Judicial Review in Indonesia Corruption Cases - Prija Djatmika; Wahbi Rahman; Dwi Edi Wibowo; Robert Lengkong Weku; Noor Dzuhaidah Osman (UIN Prof. K.H. Saifuddin Zuhri, 2026)
Indexed by (Tier 2)